5
$\begingroup$

What is the answer to this:

$$ \lim_{x\to ∞} \left({2x+3\over 2x-1}\right)^x $$

My calculator says this is $ e^2 $ but the only answer I can get to is $ 1^\infty $, which is indeterminate.

$\endgroup$
4
  • 2
    $\begingroup$ The fact that "naive" computation of the limit leads to an indeterminate form does not prevent the limit from possibly existing. For example, $\lim_{x\to 0}\frac{\sin x}{x}$ is also indeterminate of form $\frac 00$, but the limit exists. $\endgroup$ Feb 11 '16 at 15:51
  • 2
    $\begingroup$ The fact that you get an indeterminate form does not mean the limit does not exist. In fact, $$e=\lim_{x\to\infty}\left(1+\frac1x\right)^x$$ comes from an indeterminate form. $\endgroup$
    – user228113
    Feb 11 '16 at 15:51
  • $\begingroup$ I know, it's just the only answer that I got to when naively trying to calculate the limit. I'd like to know why the limit is e^2. $\endgroup$
    – user265554
    Feb 11 '16 at 15:52
  • $\begingroup$ Indeterminate means precisely that you need to compute the limit. $\endgroup$
    – orion
    Feb 11 '16 at 15:58
6
$\begingroup$

$$\lim_{x\to+\infty}\left(\frac{2x+3}{2x-1}\right)^x=\lim_{x\to+\infty}\left(\frac{2x-1+4}{2x-1}\right)^x=\lim_{x\to+\infty}\left(1+\frac{4}{2x-1}\right)^x=$$ $$\lim_{x\to+\infty}\left(\left(1+\frac{1}{\frac{2x-1}{4}}\right)^\frac{2x-1}{4}\right)^\frac{4x}{2x-1}=e^2$$

since:

I. $$\lim_{x\to+\infty}\frac{2x-1}{4}=+\infty$$

and then $$\lim_{x\to+\infty}\left(1+\frac{1}{\frac{2x-1}{4}}\right)^\frac{2x-1}{4}=e$$

II. $$\lim_{x\to+\infty}\frac{4x}{2x-1}=\lim_{x\to+\infty}\frac{4}{2-\frac{1}{x}}=2$$

$\endgroup$
3
$\begingroup$

Using the limit definition of the exponential function

$$e^z=\lim_{x\to \infty}\left(1+\frac zx\right)^x$$

we can write

$$\begin{align} \lim_{x\to \infty}\left(\frac{2x+3}{2x-1}\right)^x&=\lim_{x\to \infty}\left(\frac{1+\frac{3/2}{x}}{1+\frac{-1/2}{x}}\right)^x\\\\ &=\frac{\lim_{x\to \infty}\left(1+\frac {3/2}{x}\right)^x}{\lim_{x\to \infty}\left(1+\frac {-1/2}{x}\right)^x}\\\\\ &=\frac{e^{3/2}}{e^{-1/2}}\\\\ &=e^2 \end{align}$$

$\endgroup$
2
$\begingroup$

Consider $$A= \left({2x+3\over 2x-1}\right)^x$$ $$\log(A)=x\log\left({2x+3\over 2x-1}\right)=x\log\left(1+{4\over 2x-1}\right)$$ Now, remembering that, for small $y$, $\log(1+y)\sim y$ $$\log(A)\sim x \times {4\over 2x-1}={4x\over 2x-1}\sim {4x\over 2x}=2$$

$\endgroup$
1
$\begingroup$

$$\left(\frac{2x+3}{2x-1}\right)^x=\left(\frac{1+\frac{3}{2x}}{1+\frac{-1}{2x}}\right)^x=\frac{\left[\left(1+\frac{1}{\frac{2x}{3}}\right)^{\frac{2x}{3}}\right]^{\frac{3}{2}}}{\left[\left(1+\frac{1}{-2x}\right)^{-2x}\right]^{\frac{-1}{2}}}$$

Now, noting that$\left(1+\frac{1}{y}\right)^y\to e$ as $\vert y \vert \to \infty$, we can take $y=\frac{2x}{3}, -2x$ in the numerator and denominator respectively to see that this limit tends to $\frac{e^{\frac{3}{2}}}{e^{\frac{-1}{2}}}=e^2$ as required.

$\endgroup$
0
$\begingroup$

$$\left(\frac{2x+3}{2x-1}\right)^x=\exp\left(x\ln\left(1+\frac{4}{2x-1}\right)\right)$$

We have $\ln\left(1+\frac{4}{2x-1}\right)=\frac{4}{2x-1}+o_{+\infty}\left(\frac{1}{x}\right)$.

Then $x\ln\left(1+\frac{4}{2x-1}\right)=\frac{4x}{2x-1}+o(1)\to 2$ as $x\to+\infty$.

Hence $\lim\limits_{x\to +\infty}\left(\frac{2x+3}{2x-1}\right)^x=e^2$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.